化简[(tanθ*sinθ)/(tanθ-1)] +[ cosθ/(1-tanθ) ]
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 11:58:34
化简[(tanθ*sinθ)/(tanθ-1)]+[cosθ/(1-tanθ)]化简[(tanθ*sinθ)/(tanθ-1)]+[cosθ/(1-tanθ)]化简[(tanθ*sinθ)/(tanθ
化简[(tanθ*sinθ)/(tanθ-1)] +[ cosθ/(1-tanθ) ]
化简[(tanθ*sinθ)/(tanθ-1)] +[ cosθ/(1-tanθ) ]
化简[(tanθ*sinθ)/(tanθ-1)] +[ cosθ/(1-tanθ) ]
原式=(cosθ-tan²θcosθ)/(1-tanθ)
=cosθ(1+tanθ)(1-tanθ)/(1-tanθ)
=cosθ+sinθ
[(tanθ*sinθ)/(tanθ-1)] +[ cosθ/(1-tanθ) ]
=[(sinθ/cosθ*sinθ)/(sinθ/cosθ-1)] +[ cosθ/(1-sinθ/cosθ) ]
=[sin^2θ/(sinθ-cosθ)] +[ cos^2θ/(cosθ-sinθ) ]
=[sin^2θ/(sinθ-cosθ)] -[ cos^2θ/(sinθ-cosθ...
全部展开
[(tanθ*sinθ)/(tanθ-1)] +[ cosθ/(1-tanθ) ]
=[(sinθ/cosθ*sinθ)/(sinθ/cosθ-1)] +[ cosθ/(1-sinθ/cosθ) ]
=[sin^2θ/(sinθ-cosθ)] +[ cos^2θ/(cosθ-sinθ) ]
=[sin^2θ/(sinθ-cosθ)] -[ cos^2θ/(sinθ-cosθ) ]
=(sin^2θ-cos^2θ)/(sinθ-cosθ)
=(sinθ+cosθ)(sinθ-cosθ)/(sinθ-cosθ)
=(sinθ+cosθ)
收起
化简[(tanθ*sinθ)/(tanθ-1)] +[ cosθ/(1-tanθ) ]
求证 tanθ(1+sinθ )+sinθ /tanθ (1+sinθ )-sinθ =tanθ+sinθ/tanθsinθ
化简tan(45-θ)×tan(45+θ)
化简(sinθ-cosθ)/(tanθ-1)A.tanθ B.sinθ C.-sinθ D.cosθ
化简(sinθ-cosθ)/(tanθ-1)
化简tanθ-1分之sinθ-cos等于
若兀/4tanθB.cosθ>tanθ>sinθC.sinθ>tanθ>cosθD.tanθ>sinθ>cosθ
求证:tan²θ-sin²θ=tan²θ·sin²θ
求证tan^2θ-sin^2θ=tan^2θsin^2θ
已知sinθcosθ>0 sinθtanθ
化简1-sin2θ/cos²θ-sin²θ=1-tanθ/1+tanθ
化简:cos^2θcotθ+sin^2θtanθ+2cosθsinθ
化简 1、cosθ*tanθ 2、 (1-sinθ)(1+sinθ)
化简 tan2θ-tanθ/1+tan2θtanθ
若tanθ+1/tanθ=3则sinθ·cosθ=
三角函数:1+tan²θ=tanθ/sinθcosθ
[sin(180°)-θsin(270°- θ)tan(90°- θ)]/[sin(90°+ θ)tan(270°- θ)tan(360°- θ)]
化简:cosθtanθ